2018
DOI: 10.1123/jsep.2017-0306
|View full text |Cite
|
Sign up to set email alerts
|

In It Together: A Qualitative Evaluation of Participant Experiences of a 10-Week, Group-Based, Workplace HIIT Program for Insufficiently Active Adults

Abstract: Using guidance from the reach, efficacy, adoption, implementation, and maintenance evaluation framework, we aimed to qualitatively evaluate the participant experiences of a workplace high-intensity interval training (HIIT) intervention. Twelve previously insufficiently active individuals (four males and eight females) were interviewed once as part of three focus groups. Perceptions of program satisfaction, barriers to and facilitators of adherence, and persistence to exercise were explored. HIIT initiates inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 46 publications
5
62
0
2
Order By: Relevance
“…Table 2 presents an overview of the included studies. Three of the eight studies were undertaken in the United States [3234, 39], three in Denmark [35, 38, 40], and two in the United Kingdom [36, 37]. The studies were published between 2013 and 2018.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 presents an overview of the included studies. Three of the eight studies were undertaken in the United States [3234, 39], three in Denmark [35, 38, 40], and two in the United Kingdom [36, 37]. The studies were published between 2013 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 2013 and 2018. Four studies were qualitative [32, 33, 36, 39, 40], one study was quantitative [38], and three studies were mixed-methods [34, 35, 37]. The reports included a total of 2,686 participants with a range of 41–1,260 participants per study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the novel virtual-monitoring system may have positively influenced the findings of this study, contributing to the high adherence observed. Previous work in sedentary individuals has shown that immediate feedback illustrating HR can positivity influence participant motivation (Kinnafick et al 2018). Allowing the research team to provide feedback to participants throughout the intervention also probably improved motivation by creating a supportive environment (Petit & Cambon, 2016).…”
Section: Myocyte Adaptationsmentioning
confidence: 99%